IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA PADA TEMA GAYA HIDUP BERKELANJUTAN KELAS IV SDN 10 KARANGGONDANG - Putri Dwi Damayanti; Wulan Sutriyani; Erna Zumrotun (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The background of this study is the minimal implementation of the project to strengthen the Pancasila student profile (P5) at SDN 10 Karanggondang. The purpose of this study is to describe how teachers implement P5 in class IV and identify the obstacles faced by classroom teachers. The researcher used a qualitative descriptive method. Data was collected through observation, interviews, questionnaires, and documentation. Data analysis was conducted using the Miles and Huberman model with data reduction, data presentation, and conclusion drawing stages. The results show that P5 implementation includes planning, implementation, and evaluation. Obstacles in its implementation are the lack of training and the absence of the facilitation team in project planning, resulting in teachers' lack of understanding of P5.